Serial PET-CT Scans Can Help Determine Duration of Antibiotic Therapy After Endovascular Mycotic Thoracic Aortic Aneurysm Repair. (August 2019) - Weissmann, Jonathan; Shnaker, Ali; Mahajna, Shadi; Ajaj, Moanis; Fajer, Simone
Mycotic aortic aneurysm is a rare vascular condition, with high-risk for fatal complications. In cases of bacterial infection, prolonged antibiotic therapy is administered. There is no consensus on duration of antibiotic therapy and close follow-up is recommended following surgical and endovascular interventions. We report a case of a patient, who was diagnosed with mycotic aneurysm and underwent successful endovascular repair. Extended postoperative antibiotic treatment was administered. The duration was determined by sequential Fluorine-18 fluorodeoxyglucose positron emission tomography-computed tomography (PET-CT) scans over a period of 6 months.